ECONOMIC EFFECTS OF TECHNOLOGICAL DEVELOPMENT AND THE INTERNATIONAL DIVISION OF LABOR - Sahar Kareem Gatae Ali (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: In this study, the impact of technological development and international division of labor is analyzed on the basis of annual panel data for 12 developed and emerging economies in the years 2000 to 2023. Method: The empirical design relates the level of economic performance (GDP per capita PPP) to three indicators of technological upgrading and countries' positions in international production structures, namely, high-tech exports, ICT goods exports, and medium and high-tech exports. The study uses a panel PMG-ARDL framework as a result of the tests of cross-sectional dependence and panel unit root. Results: It can be concluded from the results that in both the long run and the short run, high-technology exports, ICT goods exports and medium- and high-technology exports have positive and statistically significant effects on GDP per capita. The error correction coefficient is negative and statistically significant, indicating that a stable adjustment process to long run equilibrium exists. There are also distinct country specific effects and indeed there is clear heterogeneity between advanced industrial economies, emerging manufacturing and Arab emerging economies. The results show that technological development has impacts on economic growth not only on the domestic innovation capacity but also by its linkage to the supply of foreign capital and specialize in higher value-added activities. Novelty: The study concludes that countries wanting to boost their income levels ought to be coordinated in technological policy, export upgrading, ICT trade capability, and involvement in global value chains in a single integrated development strategy.